Estimating the economic burden posed by work-related violence to society: A systematic review of cost-of-illness studies. (July 2019) - Hassard, Juliet; Teoh, Kevin R.H.; Cox, Tom
Highlights: The economic burden posed to society by work-related violence is sizable, but likely undervalued. Existing economic estimates are dated, examine few national contexts, and consider a limited range of costs. The 'sharp-end' of exposure to violence is accurately accounted in COI studies. 'Hidden' forms of violence are not well represented in economic estimates. A limited range of productively-related and intangible costs are accounted for. Abstract: Estimates of the economic burden on society posed by work-related violence are important and often highly cited sources of evidence; typically used to substantiate arguments for prevention. However, such sources of information are generally poorly understood and seldom critiqued outside the disciplines of health economics and public health. The objective of this systematic review is to collate, review and synthesize evidence-based economic estimations of the burden on society of work-related violence. A research protocol was developed and peer-reviewed a priori, examining both the academic and grey literatures. Ten cost-of-illness studies met the inclusion criteria and were reviewed. All studies used a bottom-up (person-based) approach to derive their economic estimates, with only two national-contexts examined. In general, a limited number of indirect (productivity-related) and intangible cost components were accounted for in the cost-of-illness studies. The reviewed studies were notably dated, with only two published post-2010. The derived economic estimates ranged from $ 2.36 million to $ 55.86 billion (figures inflated to 2016 US dollars). We conclude that much of the available evidence provides an informative, but possibly dated estimate, of the cost of incidents of work-related violence at the 'sharp-end' of exposure. Possibly such estimates are gross under-valuations, under-representing the true burden to society. This first systematic review in the area identifies key limitations in the operationalization and measurement of the construct of work-related violence within cost-of-illness studies. We argue such critiques should frame and deepen our understanding of economic estimates in this domain. Future directions are discussed.